Agribisnis Komoditi Perikanan Unggulan Di Kota Pekanbaru - Shinta Utiya Syah (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2016)
Pekanbaru city has potential to be developed into a fisheries business, in addition to industry and other fields. This potential is characterized by the availability of land and water resources for the development of inland fisheries agribusiness. Leading fishery commodity is a commodity that has both competitively as well as comparatively superior value. The purpose of this paper was to identify the development of agri-fishery commodities featured in the Pekanbaru. Results of the analysis showed that the potential fishery commodities in Pekanbaru were patin, catfish, and tilapia. Agribusiness development fishery commodities that superior to commodity production of patin was located in the District Bukit Raya, Tampan and Payung Sekaki. Sentra of catfish was in Tampan, Bukit Raya and Payung Sekaki. Sentra of tilapia was in District Bukit Raya, Tampan and Payung Sekaki.